Advances in Production Management Systems. Competitive Manufacturing for Innovative Products and Services IFIP WG 5.7 International Conference, APMS 2012, Rhodes, Greece, September 24-26, 2012, Revised Selected Papers, Part I - Emmanouilidis, Christos; Taisch, Marco; Kiritsis, Dimitris; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The two volumes IFIP AICT 397 and 398 constitute the thoroughly refereed post-conference proceedings of the International IFIP WG 5.7 Conference on Advances in Production Management Systems, APMS 2012, held in Rhodes, Greece, in September 2012. The 182 revised full papers were carefully reviewed and selected for inclusion in the two volumes. They are organized in 6 parts: sustainability; design, manufacturing and production management; human factors, learning and innovation; ICT and emerging technologies in production management; product and asset lifecycle management; and services, supply chains and operations.
Energy Efficient Manufacturing -- Sustainable Value Creation, Business Models and Strategies -- Mass Customization -- Products of the Future and Manufacturing Systems Design -- Advanced Design, Manufacturing and Production Management -- Robotics in Manufacturing -- Modern Learning in Manufacturing and Production Systems -- Human Factors, Quality and Knowledge Management -- Innovation in Products and Services in Developing Countries.
Keywords: Computer science; Information systems; Artificial intelligence; Management information systems; Computer Science; Computer Appl. in Administrative Data Processing; Information Systems and Communication Service; Artificial Intelligence (incl. Robotics).; Business Information Systems